PENGARUH SHOLAT KHUSYU’ TERHADAP PENURUNAN TEKANAN DARAH PADA PENDERITA HIPERTENSI DI DUSUN JANGAR DESA NGARJO KECAMATAN MOJOANYAR KABUPATEN MOJOKERTO - Achwandi, Moch. (JURNAL KEPERAWATAN BINA SEHAT, 2015)
Prayers is a worship required of Muslims. Prayers can be a meditation that can induce the relaxation response. Relaxation can affect blood pressure in hypertensive patients but is not yet known whether the prayer relaxation can lower blood pressure. The purpose of this study was to determine the effect of prayer is there humility to the reduction of blood pressure in patients with hypertension. This research method using pre-experimental design (One group pretest-posttestdesign). This study uses a sampling technique Nonprobability Sampling with Purposive Sampling types. Total population of 80 respondents and the amount of sample is 10 respondents who fit the inclusion criteria. Data collection techniques by observation accuracy the presence of prayer and tensimeter. The results showed a majority of 10 respondents have hypertension stage 2 by 5 respondents (50%) before performing prayers and 5 respondents (50%) were on previously normal blood pressure blood pressure are at stage 1 stage 2 and stage 3 after prayers. The result of analysis by using paired T-tes on systolic blood preasure before and after the prayer humility’ obtained p=(0,193) over α=(0,05) so that it can be concluced Ho accepted and H1 rejected, which means there is no effect of prayer humility’ against the decline in systolic blood pressure in patient with hypertension. Whereas the results of analysis by using paited T-test on diastolic blood pressure before and after the prayers humility obtained p=(0,003) is less than α=(0,05) so that it can be concluced Ho rejected, which means there is the influence of prayer humility to decrease the pressure diatolic blood in patient with hypertension in Hamlet Village Jangar Ngarjo Mooanyar District of Mojokerto. Patients with high blood pressure or hypertension can perform their prayers were done in humilit as a therapy to keep blood pressure remained stable.Keywords: Prayer Humility, Blood Pressure, Hypertension